Aseptic meningitis and myelitis as presenting features of SLE. Issue 6 (19th October 2021) - Sharma, Archana; Vibha, Deepti; Singh, Rajesh Kumar; Elavarasi, Arunmozhimaran; Ramanujam, Bhargavi; Garg, Ajay; Tripathi, Manjari
Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disorder affecting multiple organs of body. We present a case having history of fever, headache, vomiting for 1 month, and quadriparesis with urinary retention and constipation for 5 days. MRI brain contrast showed T2/FLAIR hyperintensities in the region of bilateral cingulate gyri and midbrain with focal meningeal thickening in the region of falx and long segment myelitis in C2 to C7 with cord expansion. In view of atypical imaging findings, she was evaluated for autoimmune and inflammatory conditions besides infective causes and was diagnosed to have SLE. In our case, aseptic meningitis and myelitis were the presenting feature that led to the diagnosis of SLE. We should be aware of the uncommon association of aseptic meningitis and myelitis in SLE patients.